Letters of Recommendation of Sidonius Apollinaris – the Legacy of Tradition and the Challenge of Transformations - Skibiński, Tomasz (Saeculum Christianum. Pismo Historyczne, 2021)
The article presents the letters of Sidonius Apollinaris - Gallo-Roman aristocrat, poet and bishop. The study aims at analysing the letters of Sidonius from the point of view of their purpose, the models used, the argumentation, and the list of recipients to whom the letters are addressed. On the one hand, it shows that Sidonius remaining faithful to his masters in epistolography (Cicero, Pliny the Younger, Symmachus), while on the other hand, was able to change the form of letters according to the situation. The paper also allows us to discern the changes that took place in the works of Sidonius after his ordination.